BELAJAR BERBASIS ANEKA SUMBER DALAM PENDIDIKAN NONFORMAL - B. P. Sitepu (JIV-Jurnal Ilmiah Visi, 2011)
Paradigm shift in education has made significant change in the roles of teacher and student in teaching and learning process. In the new paradigm the student become the axis of teaching and learning process. The student makes the choice in learning objective, learning materials, and learning resources based on his/her learning style. The teacher acts more as a learning designer, learning manager, and tutor. The learning theory development tends to provide the learner with learning skills to enable them to be independent learners to life-long learning. However, the learning theories are mostly discussed in the formal eduacation situation, though the theories are also apllicable for nonformal education. This article discusses how the current learning theories can be implemented in nonformal education. The discussion is limited on the application of learning resources development in early childhood education and learning community centers. The discussion ends with a strong conclusion that resources based learning theory are potential and need to apply in nonformal education under a condition that there should be some changes in the roles of teachers/instructors, learners, and the nonformal institution.